Navigating new territory: discourses of assessment moderation in UAE higher education - Alsharefeen, Rami; Al Sayari, Naji; Al-Deaibes, Mutasim (Frontiers in Education, 2025)
IntroductionThis study investigates faculty perceptions of discourses associated with assessment moderation at a higher education institution in the UAE.MethodologyThis study employed a survey incorporating closed- and open-ended components. Adie and her associates' (2013) framework of assessment moderation discourses was used as an analytical framework for qualitative data with the purpose of identifying the discourses faculty associate with the purposes of assessment moderation practice at the target institution.ResultsThe findings revealed community building as the most dominant discourse among faculty responses. Significantly, the study identified a fifth discourse category extending beyond the existing four-category framework: faculty resistance characterized by minimal or negligible valuation of assessment moderation practices. Approximately 25% of respondents questioned the fundamental pedagogical or institutional value of assessment moderation, suggesting theoretical gaps in current frameworks that assume universal acceptance of moderation principles.DiscussionThese findings advance assessment moderation theory by identifying a distinct faculty discourse characterized by the perception of minimal or negligible value in the moderation process. The study demonstrates that theoretical frameworks developed in Western educational contexts require substantial adaptation for diverse cultural and institutional settings. The research has significant implications for policy development and implementation of assessment moderation practices in higher education environments, highlighting the need for culturally responsive approaches to quality assurance in global academic settings.